Fungicide efficacy of nanocrystal-based formulations against peanut smut - Camiletti, Boris Xavier; Paredes, Juan Andrés; Monguillot, Joaquin Humberto; Grosso, Nelson R.; Rago, Alejandro Mario (Elsevier, 2021)
Nanocrystal-based formulations were investigated as a novel technology to increase the fungicide efficacies of azoxystrobin (AZY), cyproconazole (CYP), and their combination (AZY + CYP) against peanut smut caused by Thecaphora frezii. The nano-sized formulations were compared with commercially-available formulations according to their performance under laboratory, semi-controlled, and field conditions. During in vitro assays, the reductions in EC50 values evidenced the superior antifungal activity of nanocrystals against T. frezii. Based on disease incidences and severities observed in experiments under semi-controlled conditions, nano-based formulations containing cyproconazole (CYP) and its combination provided better control of peanut smut than their respective conventional formulations. Nano-sized formulations containing CYP and AZY + CYP also provided similar control when applied at half-rate and showed potential for reducing the amount of fungicide applied to the field. A remarkable variation in peanut smut epidemics was observed in field experiments. During the first year of experiments, only the nano-based formulations containing AZY and AZY + CYP provided significant disease control. However, formulations with CYP produced the lowest degree of disease incidence and severity in the subsequent growing season, although no differences among formulations were observed. Based on this study, nanocrystals have demonstrated potential to enhance the performance of fungicides currently used to control peanut smut.